Efficacy and safety of a third stereotactic radiosurgery for recurrent trigeminal neuralgia: an international, multicenter study - De Nigris Vasconcellos, Fernando; Alzate, Juan Diego; Mashiach, Elad; Meng, Ying; Santhumayor, Brandon; Bernstein, Kenneth; Pichardo-Rojas, Pavel; Dono, Antonio; Damron, Ethan P; Blanco, Angel I; Esquenazi, Yoshua; Urgosik, Dusan; et al. (Acta neurochirurgica, 2024)
BACKGROUND AND OBJECTIVES: Trigeminal Neuralgia (TN) is a debilitating facial pain disorder, often necessitating surgical interventions when medication proves insufficient. Stereotactic Radiosurgery (SRS) is an established therapeutic option. Limited studies explored the feasibility of a third SRS procedure. Our study investigates the safety and efficacy of a third SRS procedure for recurrent TN. METHODS: We performed a retrospective analysis across multiple centers using databases collected prospectively. Pain status was evaluated utilizing the BNI Pain Intensity Scales. The Kaplan-Meier method was employed to estimate the time to recurrence, with group comparisons conducted using log-rank tests. Associations were explored using Chi-square and logistic regression models. RESULTS: Ten institutions contributed with a total of 35 patients. A third SRS revealed sustained effectiveness with a pain control rate of 82.7%. The median time to recurrence was 35.5 months. New sensory dysfunction following the third procedure occurred in 22% of patients who had preserved sensory function after the second procedure. When considering those who developed sensory dysfunction after the second procedure, 40% of the entire cohort was affected. There were no significant differences in pain recurrence intervals among the three procedures. A meta-analysis, combining data from previous studies, showed that 89.6% of patients achieved some degree of pain control after a third SRS, with 27.4% experiencing new sensory dysfunction and a median time to recurrence of 31.6 months. CONCLUSION: Our study, the largest on the topic, affirms the sustained effectiveness of a third SRS for TN, providing comparable pain relief to initial procedures. Notably, an extended pain-free interval after the third SRS session was observed. Facial sensory dysfunction emerged as the primary side effect. Larger studies are warranted to explore correlations with demographics and treatment parameters for a comprehensive understanding of repeat SRS in managing recurrent TN.
Keywords: recidiva; Humans; lidé středního věku; Female; Aged; dospělí; výsledek terapie; senioři; lidé; reoperace; neuralgie trigeminu; radiochirurgie; Adult; Radiosurgery; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Treatment Outcome; Aged, 80 and over; Recurrence; Trigeminal Neuralgia; senioři nad 80 let; retrospektivní studie; mužské pohlaví; Reoperation